The coupling dynamic effect of government environmental attention, green efficiency, and air quality - Yuequn Cao; Chaoyang Tu; Kexin Du; Chenlin Cui (Humanities & Social Sciences Communications)
Abstract There exists a significant interactive coupling relationship between the government’s environmental attention, green efficiency, and air quality. Studying the dynamic coupling effects among these variables is crucial for promoting the sustainable development of China’s economy and society. This paper clarifies the coupling mechanism of government environmental attention, green efficiency, and air quality by analyzing 270 prefecture-level cities in China using the coupling coordination model and PVAR model. The results indicate that while government environmental attention, green efficiency, and air quality all show an upward trend, their temporal and spatial performances differ. The degree of coupling and coordination among these variables also exhibits significant fluctuations, indicating a dynamic relationship. Government environmental attention as a fundamental driving force in the dynamic coupling of these variables, promoting high-level development through factors like economic growth, technological progress, and socio-cultural influences. Finally, this paper proposes five key policy recommendations. The study provides valuable insights into promoting local governments’ environmental initiatives, advancing China’s ecological civilization, and addressing international environmental pollution in developing countries.